Evidence for Air-Seeding: Watching the Formation of Embolism in Conifer Xylem - Mayr, S. (J Plant Hydraul, 2014)
Water transport in plants is based on a metastable system as the xylem “works” at negative water potentials (ψ). At critically low ψ, water columns can break and cause embolism. According to the air-seeding hypothesis, this occurs by air entry via the pits. We studied the formation of embolism in dehydrating xylem sections of Juniperus virginiana (Cupressaceae), which were monitored microscopically and via ultrasonic emission analyses. After replacement of water by air in outer tracheid layers, a complex movement of air-water menisci into tracheids was found. With decreasing ψ, pits started to aspirate and the speed of menisci movements increased. In one experiment, an airseeding event could be detected at a pit. The onset of ultrasonic activity was observed when pits started to close, and ultrasonic emission ceased at intense dehydration. Experiments clearly indicated that predictions of the air-seeding hypothesis are correct: At low ψ, pit mechanisms to prevent air entry failed and air spread into tracheids. ψ fluctuations caused complex movements of air-water menisci and pits, and at low ψ, air-seeding caused ultrasonic emissions. Main insights are presented in a video.